Analysis of factors influencing electric vehicle adoption in Sub-Saharan Africa using a modified UTAUT framework - Qasim Ajao; Makhluk Hossain Prio; Lanre Sadeeq (Discover Electronics)
Abstract Electric vehicles (EVs) powered by renewable energy are central to achieving Sustainable Development Goal (SDG) 7.2, which aims to increase the share of renewable energy and reduce carbon emissions in the transportation sector. A 2023 projection estimated that EV sales in leading EV-importing Sub-Saharan African (SSA) countries, including Nigeria, Ethiopia, South Africa, Kenya, Rwanda, Mauritius, and Seychelles, would exceed 700 million units within 5 years and grow to 4 million by 2037. Despite these optimistic forecasts, the current adoption rate of EVs in SSA remains significantly low. This study extends the Unified Theory of Acceptance and Use of Technology (UTAUT) framework to identify key factors influencing EV adoption in the region. The model incorporates facilitating conditions, trust, performance expectancy, social influence, network externalities, and effort expectancy as critical determinants. Empirical results reveal that facilitating conditions (H6) have a 30% stronger effect on behavioral intentions compared to network externalities (H5). These findings highlight the need for robust infrastructure, supportive policies, and favorable conditions to accelerate EV adoption in SSA and shape EV purchase decisions. The paper concludes by discussing the empirical results and proposing directions for future research to deepen understanding of EV adoption dynamics in the region.